Формування мережі земських лікарняно-продовольчих пунктів на Катеринославщині та їх діяльність на початку ХХ ст. - Шляхов, О.Б. (Проблеми історії України ХІХ – початку ХХ ст., 2016)
Висвітлено питання формування мережі земських лікарняно-продовольчих пунктів у Катеринославській губернії наприкінці ХІХ — на початку ХХ ст., основні напрями їх діяльності з соціального захисту робітництва. Освещены вопросы формирования сети земских врачебно-продовольственных пунктов в Екатеринославской губернии в конце ХІХ — начале ХХ в., основные направления их деятельности по социальной защите рабочего класса. The article elucidates the questions of forming the network of medical-food points in
Ekaterinoslav Governorate in the late nineteenth — early twentieth centuries. To 1903
nineteen points of this type had functioned in the territory of the province. The author reveals
the main directions of their activity aimed at social protection of working class and, in
particular, providing the workers with food and medical assistance and accommodation. It is
also noted that these points played the role of labor exchanges, assisting the workers who left
the village to get the required work. Besides that, the points were provided with small libraries
which contributed to enlightenment of the workers and their cultural development. The author
comes to the conclusion that in spite of all the deficiencies in the work of land medical-food
points they played a definite positive role in the questions of social protection of regional proletariat.